Frequency of Angles Malocclusion, Psychological Effects in Patient Using Oasis Questionnaire and Treatment Needs in Patients Visiting Dental Teaching Hospital: Malocclusion and Psychological Impact - Arshad, Saira; Khan, Ariffullah; Gulfam, Faiza; Shafiq, Seema; Ahmad, Haseeb; Arbab, Kanwal Nazir; Malik, Ayesha (Pakistan Journal of Health Sciences, 2025)
A person’s psychological health and confidence are greatly influenced by their facial appearance. It encourages acceptance, integration, and social recognition. Objective: The objective of current study was to establish the frequency of Angle’s malocclusion, assess its psychological impact using the OASIS questionnaire, and evaluate orthodontic treatment need using the Index of Orthodontic Treatment Need (IOTN) in patients visiting dental teaching hospital. Methods: Both gender patients between 14-20 years, fully erupted first molar from one arch to another were included while participants with a history of jaw injuries, experiencing orthodontic treatment, or had prior orthodontics treatment were not included in the current study. The Oral Aesthetic Subjective Impact Scale (OASIS), self-evaluation validated tool was used to determine perceived therapeutic requirements. Index of Orthodontic Treatment Need (IOTN) index was also reported. Results: Among the 350 people examined, 70% (245) were females and 30% (105) were males. The mean age was 17 years with S.D ± 1.26. 54 (15.4%) of the patients had normal dental occlusions, 175 (50%) had class I malocclusion, 99 (28.3%) had class II, and 22 (6.3%) had class III malocclusion. 202 (57.7%) of patients reported good psychological well-being about their dental looks, whereas 90 (25.7%) and 58 (16.6%) had satisfactory and poor psychological well-being respectively, based on sample size. Conclusions: This study showed a significant rate of malocclusion, with Class I being the most frequent. Psychological effects were obvious, as many patients expressed unhappiness with their oral look.